AP-2δ is a crucial transcriptional regulator of the posterior midbrain. - Katrin Hesse (Public Library of Science (PLoS), 2011)
Ap-2 transcription factors comprise a family of 5 closely related sequence-specific DNA binding proteins that play pivotal and non-redundant roles in embryonic organogenesis. To investigate the function of Ap-2δ, wδe analyzed its expression during embryogenesis and generated Ap-2δ-deficient mice. In line with the specific expression pattern of Ap-2δ in the mesencephalic tectum and the dorsal midbrain, Ap-2δ-deficient mice failed to maintain the colliculus inferior, a derivative of the dorsal midbrain, as a consequence of increased apoptotic cell death. To identify specific Ap-2δ target genes in cells of the developing dorsal midbrain, we performed whole genome analysis of cDNA expression levels. This approach identified a set of 12 putative target genes being expressed in the developing midbrain, including the transcription factors Pitx2, Mef2c, Bhlhb4 and Pou4f3. Using chromatin immunoprecipitation (CHIP) we showed that some of these genes are direct targets of Ap-2δ. Consistently, we demonstrate that Ap-2δ occupies and activates the Pou4f3 and Bhlhb4 promoters. In addition, known Pou4f3 target genes were downregulated in the posterior midbrain of Ap-2δ-deficient mice. Despite the absence of a central part of the auditory pathway, the presence of neuronal responses to sounds in the neocortex of Ap-2δ-deficient mice indicates that auditory information from the brainstem still reaches the neocortex. In summary, our data define Ap-2δ as an important transcription factor, specifying gene expression patterns required for the development of the posterior midbrain.